CHALLENGES AND THE STEPS FORWARD TO THE APPLICATION OF IJARAH (LEASING) PRODUCTS OF JAIZ BANK PLC IN NIGERIA - Wale Lateef, Adeyemo; Abdul Shukor, Dr. Syahirah; Ahmad Tajudin, Dr. Amalina (IJRDO - Journal of Business Management, 2017)
The benefits of Islamic banking in the contemporary society cannot be overemphasized, especially if its operations are in line with Sharĩ‘ah. Meanwhile, one of the Jaiz Bank Plc products is ʼIjãrah (leasing). The application of ʼIjãrah (leasing) product of Jaiz Bank Plc is faced with many problems. The paper also provides the solutions to the problems. In doing this, the challenges confront Jaiz Bank Plc can be categorized into institutional and operational challenges, it benefits will outweigh the challenges, once the challenges are overcome. This paper also examines the principles of ʼIjãrah (leasing) products and how it is being structured by Sharĩ‘ah. The paper discusses that once the regulatory authorities address the framework, the operational challenges will be solved.